Body mass index in dementia - García-Ptacek, S; Faxén-Irving, G; Cermáková, P; Eriksdotter, M; Religa, D (European journal of clinical nutrition, 2014)
This review comprehensively examines the current knowledge on the relationship between body mass index (BMI) and dementia. The association between BMI and cognition is complex: in younger adults, higher BMIs are associated with impaired cognition. Overweight and obesity in middle age are linked to increased future dementia risk in old age. However, when examined in old age, higher BMIs are associated with better cognition and decreased mortality. Little is known about the optimal BMI for well-being and survival in populations already suffering from dementia. Lifetime trends in weight, rather than single measures, might predict prognosis better and help untangle these apparent contradictions. Thus, the need arises to properly monitor BMI trends in affected dementia patients. Registries can include BMI, improving the management of dementia patients throughout the whole course of the disease. The role of central obesity and systemic inflammation on brain pathology and cognitive decline are discussed in this review. Understanding the life-course changes in BMI and their influence on dementia risk, cognitive prognosis and mortality after diagnosis may provide new insights into the underlying pathophysiology of dementia and shape possible intervention and treatment strategies.
Keywords: obezita; Sex Factors; nutriční stav; Humans; demence; index tělesné hmotnosti; Body Mass Index; kognice; Female; rizikové faktory; stárnutí; lidé; Aging; Nutritional Status; sexuální faktory; ženské pohlaví; Male; Dementia; Obesity; Body Weight; tělesná hmotnost; mužské pohlaví; Cognition; Risk Factors